A cadaveric study on anatomical variations of kidney and ureter in India - Choudhary, Umesh; Kumar, Saroj; Jee, Kanhaiya; Singh, Anand; Bharti, Priyanka (International Journal of Research in Medical Sciences, 2017)
Background: The kidneys are a pair of bean - shaped organ located in the back of the abdomen between the 12th thoracic and 3rd lumbar vertebrae. Each kidney is about 4 or 5 inches long - about the size of a fist. The objective of this study was to study the major anatomical variations of kidney and urinary tract. Methods: The study was conducted during routine dissections of 32 cadavers over a period of 5 years. All specimens included in the study was adult cadavers of which 20 were males and 12 were females. Results: Out of 32 cadavers, 1 cadaver showed bilateral and 2 showed unilateral (2 L) lobulated kidney, 2 cadavers showed unilateral (1 L,1 R) and 1 showed bilateral accessory renal artery. 2 cadavers showed unilateral (1 L,1 R) incomplete double ureter. Conclusions: 12.5% of the cadavers showed anatomical variations in kidney and 6.25% showed bifid ureter. The knowledge of anatomical variations of kidney and ureter is of great importance for surgical, radiological and academic perspective. Hence, the early detection may be helpful in better management and increased survival rates.